Respons Aliansi Ulama Madura (AUMA) terhadap Dinamika Politik Keagamaan di Pamekasan Madura - Ali Topan (IAIN Madura, 2022)
Abstract Political-religious being a social dynamic cannot be separated from our lives as social and religious beings. In the social and cultural context of the Madurese, ulama are important actors in the social life of the Madurese in resolving conflicts and eradicating ideas that are not in accordance with Islamic teachings and state ideology. The presence of the ulama here, apart from being a preacher, also acts as an intermediary in regulating the lives of the Madurese wabil people specifically in Pamekasan. Social phenomena that occur in Pamekasan Madura are always responded quickly by the Madurese ulama alliance as a movement with the aim of controlling and regulating the symptoms that occur in the Pamekasan community. such as, closing nightclubs and tourist attractions that are not in accordance with Islamic law and the existing culture in Madura. The pattern of movement used by the Madura Ulama Alliance (AUMA) in responding to political-religious issues uses persuasive, preventive and repressive patterns. The impact of this movement is evidence that in Pamekasan there is minimal escalation of political-religious conflict compared to other regions, this is in line with the Pamekasan district jargons